2000
DOI: 10.1046/j.1365-3164.2000.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial flora and antimicrobial susceptibility patterns from dogs with otitis media

Abstract: This study evaluated the middle ear microbial¯ora and antimicrobial susceptibility patterns from dogs with otitis media. Antimicrobial susceptibility patterns were obtained on 164 micro-organisms from 107 ears of 82 dogs with otitis media that presented to Louisiana State University over a 12-year period. The most common micro-organisms isolated were Staphylococcus intermedius (26.8%), Pseudomonas aeruginosa (23.2%), b-haemolytic streptococcus (12.8%), Proteus spp. (11.0%) and Staphylococcus epidermidis (8.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 12 publications
3
27
1
5
Order By: Relevance
“…The results of this study are similar to other described in the literature (2,3,4). Although some studies have considered cogulase-negative Staphylococci to be the main bacterial agent in canine otitis (6), in the present study CPS were the most common isolated agents.…”
supporting
confidence: 93%
“…The results of this study are similar to other described in the literature (2,3,4). Although some studies have considered cogulase-negative Staphylococci to be the main bacterial agent in canine otitis (6), in the present study CPS were the most common isolated agents.…”
supporting
confidence: 93%
“…Isolates included in the study from 2011 were all collected from the ears of dogs with otitis externa, and it is well known that otic isolates tend to show higher resistance rates to several antimicrobials, including enrofloxacin and other fluoroquinolones (PETERSEN et al, 2002;WILDERMUTH et al, 2007;HARADA et al, 2012). Nevertheless, the sensitivity rate to enrofloxacin found in this study was still lower than sensitivity rates observed in other studies, where susceptibility ranged between 16% and 51% (COLOMBINI et al, 2000;MARTIN BARRASA et al, 2000;McKAY et al, 2007;WERCKENTHIN et al, 2007).…”
Section: Discussionmentioning
confidence: 49%
“…The aminoglycosides, polymyxins, detergents, and most alcohols routinely used in the treatment of the external ear canal are known to be toxic to the nervous structures of the inner ear [11]. Potentially ototoxic antimicrobial pharmaceutics are present in most topical formulations for treatment of otitis externa.…”
Section: Ototoxicitymentioning
confidence: 99%